Clinical Application of a Chromogenic Substrate Method for Determination of Factor VIII Activity - Rosén, S; Andersson, M; Blombäck, M; Hégglund, U; Larrieu, M J; Wolf, M; Boyer, C; Rothschild, C; Nilsson, I M; Sjörin, E; Vinazze, H (Thrombosis and Haemostasis, 1985)
A chromogenic substrate kit for the determination of factor VIII activity (COATEST® Factor VIII) has been evaluated in five different laboratories, one of them using a semi-automated procedure. This chromogenic method was compared to one-stage clotting assays for factor VIII determination in plasmas from healthy subjects, carriers of hemophilia A, severe, mild and moderate hemophilia A as well as von Willebrand’s patients. In all these cases, a high correlation between these two methods was obtained (r = 0.96-0.99, n = 385) with a good agreement of the assigned potencies at all levels of factor VIII. A good correlation (r = 0.94) was also obtained for the levels of factor VIII after infusion of concentrates in six severe hemophiliacs or after administration of DDAVP to von Willebrand’s patients.The chromogenic method is insensitive to preactivation of factor VIII by thrombin, thus yielding valid potency assignments also in these situations.The precision was higher with the chromogenic method than with the one-stage clotting assays (C.V. = 2-5% vs 4-15%). Altogether, the new chromogenic substrate method has proven itself suitable for determination of factor VIII in plasma and concentrates.
Keywords: Factor VIII activity assay; Chromogenic substrate kit; Clinical evaluation